Implementasi Manajemen dalam Membentuk Akhlak Remaja Masjid di Kabupaten Labuhanbatu - Rambe, Sari Endang Wahyuni; Lubis, Agus Salim; Siregar, Esli Zuraidah (Tadbir: Jurnal Manajemen Dakwah, 2025)
The background of this research is the moral condition of mosque youth in Labuhanbatu, which tends to be poor, characterized by behaviors such as gathering until late at night, addiction to online games, disobedience to parental commands, and following Western culture. This study employs a descriptive qualitative method. The informants consist of 30 individuals, including 27 primary data sources and 3 secondary data sources. The results of the research on the management of moral development in the Ikatan Remaja Masjid indicate that the moral condition of mosque youth in Dusun Parlaisan includes the influence of Western culture, late-night gatherings, addiction to online gaming, and disobedience to parents. To address these moral issues, activities such as study sessions and social events have been implemented, utilizing management functions such as planning, organizing, executing, and monitoring to support the moral development of mosque youth. The hope is that these activities can cultivate Islamic youth and serve as examples for other young people.